Evolution of Epidermal Growth Factor (EGF)-like and Zona Pellucida Domains Containing Shell Matrix Proteins in Mollusks - Shimizu, Keisuke; Takeuchi, Takeshi; Negishi, Lumi; Kurumizaka, Hitoshi; Kuriyama, Isao; Endo, Kazuyoshi; Suzuki, Michio (Molecular biology and evolution, 2022)
Abstract Several types of shell matrix proteins (SMPs) have been identified in molluskan shells. Their diversity is the consequence of various molecular processes, including domain shuffling and gene duplication. However, the evolutionary origin of most SMPs remains unclear. In this study, we investigated the evolutionary process EGF-like and zona pellucida (ZP) domains containing SMPs. Two types of the proteins (EGF-like protein (EGFL) and EGF-like and ZP domains containing protein (EGFZP)) were found in the pearl oyster, Pinctada fucata. In contrast, only EGFZP was identified in the gastropods. Phylogenetic analysis and genomic arrangement studies showed that EGFL and EGFZP formed a clade in bivalves, and their encoding genes were localized in tandem repeats on the same scaffold. In P. fucata, EGFL genes were expressed in the outer part of mantle epithelial cells are related to the calcitic shell formation. However, in both P. fucata and the limpet Nipponacmea fuscoviridis, EGFZP genes were expressed in the inner part of the mantle epithelial cells are related to aragonitic shell formation. Furthermore, our analysis showed that in P. fucata, the ZP domain interacts with eight SMPs that have various functions in the nacreous shell mineralization. The data suggest that the ZP domain can interact with other SMPs, and EGFL evolution in pterimorph bivalves represents an example of neo-functionalization that involves the acquisition of a novel protein through gene duplication.